Myogenin promotes myocyte fusion to balance fibre number and size - Massimo Ganassi (Nature Portfolio, 2018)
Loss of the transcription factor Myogenin in mice reduces skeletal myogenesis and leads to perinatal death but how Myogenin regulates muscle formation is unclear. Here, the authors show that zebrafish Myogenin enhances Myomaker expression, muscle cell fusion and myotome size, yet decreases fast muscle fibre number.